ANALISIS MATRIK IE PADA UMKM BERBASIS PRODUK PERTANIAN KELOMPOK WANITA PELAKU USAHA TANAMAN HIAS DI DESA SIDOMULYO KOTA BATU - Agustim, Warter; Nurhidayat, Moch. (Unitri Press, 2020)
This study aims to determine the right strategies to describe, analyze, and interpret the factors related to the empowerment of women's business groups so that they can improve the level of the family economy and become an independent and economically prosperous family. Strategy determination is implemented through three steps, namely the input stage (using the Internal Factor Evaluation Matrix (IFE) and External Factor Evaluation Matrix (EFE)) method, the matching stage, and the decision stage. Researchers used qualitative research methods with a participatory approach that did not do hypothesis testing only describing the state of social protection in accordance with the facts found at the study site. Data collection techniques namely using questionnaires, interviews, observation took several elements and then each element was investigated in depth. To obtain information about the profile of Ornamental Plant Business Women in Sidomulyo Village, Batu City by using accidental sampling technique. A score of 284 was obtained from the IFE matrix, while a score of 334 was obtained from the matrix. Scores on the IFE matrix and the EFE Matrix show that the Group of Ornamental Plant Business Women are in cell II, with strategies that can be used namely developing and developing, so that they are in a strong position.